Augustan accounts of the regal period - Fox, M; Fox, M. A. (1991)
﻿ This thesis examines accounts of the regal period in Cicero's de republica, Varro, Dionysius of Halicarnassus and Livy, as well as references to the period in Propertius IV and Ovid's Fasti. Cicero, Varro and Dionysius all present idealized accounts of the period, responding to the aetiological traditions concerning it, and making Rome's founders represent ideal originators, in different ways depending on the nature of their interests. Cicero acknowledges the problems of idealizing history, pointing to the influence of historical context on views of history. Dionysius' historiographical theories are examined, revealing a coherent theory in the light of which Dionysius' idealization can be seen as an informed attempt at an historical reconstruction. Livy too gives the regal period an originative function, to display in microcosm many themes important in later history. His interest in the origin of Rome's problems prevents him from idealizing the period. Instead he demonstrates political and social development under the kings which leads to a republic where the tensions of Rome's later history can be foreseen. Elegy had traditionally rejected history, but in Propertius IV history is included, much of it regal. Propertius establishes a particular relationship between the regal period and the elegist which is continued in Ovid's Fasti. Both poets reinterpret history, applying the self-conscious skill which had hitherto rejected historical material, and subverting expectations of the relationship of past to present. Ovid also displays kinship to themes of the Augustan revival, celebrating the present as the culmination of the past. The main unifying feature of all accounts is the dominance of the author's view of the present in shaping his version of history, stemming from the importance of the regal period as the period of Rome's origins. In the conclusion, these writings are placed within their Augustan context.